1986
DOI: 10.1021/jm00160a010
|View full text |Cite
|
Sign up to set email alerts
|

Opioid agonist and antagonist bivalent ligands. The relationship between spacer length and selectivity at multiple opioid receptors

Abstract: Bivalent ligands containing the oxymorphamine or naltrexamine pharmacophores connected to spacers of varying length were synthesized and evaluated for their selectivity at mu, kappa, and delta opioid receptors. The oxymorphamine bivalent ligands (1-8) behaved as mu agonists on the electrically stimulated guinea pig ileum longitudinal muscle preparation (GPI). The spacer that conferred peak agonist activity in these series contains a total of four glycyl units (n = 2). Binding studies with guinea pig brain memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 6 publications
5
111
0
Order By: Relevance
“…Similar results are seen with the hydrazide series as well. Thus, these agents do not simultaneously label two binding pockets, and their mechanism(s) of prolonged activity differ from that proposed by Portoghese for his bivalent ligands (Erez et al, 1982;Portoghese et al, 1986;Bolognesi et al, 1996).…”
Section: Mu Antagonistsmentioning
confidence: 73%
“…Similar results are seen with the hydrazide series as well. Thus, these agents do not simultaneously label two binding pockets, and their mechanism(s) of prolonged activity differ from that proposed by Portoghese for his bivalent ligands (Erez et al, 1982;Portoghese et al, 1986;Bolognesi et al, 1996).…”
Section: Mu Antagonistsmentioning
confidence: 73%
“…Several studies have suggested that bivalent ligands may bridge associated opioid receptors. Bivalent ligands of opioid alkaloids (17)(18)(19)(20)(21)(22)(23)(24) and peptide agonists derived from enkephalins (25)(26)(27)(28) have been characterized as having increased opioid receptor potency and selectivity when compared to corresponding monovalent counterparts. More recently, bivalent ligands have been used as tools to further characterize ␦ and opioid receptor phenotypes.…”
mentioning
confidence: 99%
“…All three major types (␦, , and ) of opioid receptors share high homology (ϳ60%) and a highly conserved transmembrane domain (Knapp et al, 1995;Dhawan et al, 1996;Waldhoer et al, 2004). Before the development of opioid receptor cDNAs, a number of investigations suggested that opioid receptors physically interact with one another (Erez et al, 1982;Rothman and Westfall, 1982;Portoghese et al, 1986;Porreca et al, 1992;Traynor and Elliott, 1993). With the availability of cDNAs, a great number of studies using in vitro expression systems have afforded more convincing evidence for dimerization/oligomerization of opioid receptors (Jordan and Devi, 1999;George et al, 2000;Gomes et al, 2000;Ramsay et al, 2002).…”
mentioning
confidence: 99%